THE CONTRIBUTION OF SMES ENTREPRENEURSHIP TO SOCIO-ECONOMIC DEVELOPMENT IN TERENGGANU - Yusof, Mohamed Suhaimi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Small and medium enterprises (SMEs) are widely acknowledged as the backbone of socio-economic development, particularly in emerging regions where they play a vital role in employment generation, poverty alleviation, and cultural preservation. This article explores the contribution of SMEs entrepreneurship to socio-economic development in Terengganu, Malaysia, and critically examines the constraints that limit their growth. By synthesizing recent scholarship, the study situates SME development within five central dimensions: financial accessibility, digital transformation, entrepreneurial capacity, global competitiveness, and inclusivity for women and youth. The analysis demonstrates that SMEs in Terengganu contribute to economic diversification through tourism, fisheries, handicrafts, and cultural industries while reinforcing community resilience and sustaining local identity. Yet persistent barriers such as restricted capital access, uneven digital adoption, skills deficiencies, exposure to global market pressures, and limited inclusivity undermine their potential impact. These challenges are interconnected and require integrated approaches that align institutional reforms with ecosystem-based strategies. Building on this foundation, the article proposes practical suggestions including hybrid financing models, targeted digitalization programs, localized training and mentorship, differentiation strategies rooted in cultural heritage, and inclusive entrepreneurship policies. These strategies reflect both global best practices and local realities, positioning SMEs as catalysts for sustainable development in Terengganu. The conclusion affirms that strengthening SMEs is not solely an economic agenda but a holistic pathway toward inclusive, competitive, and resilient regional growth, offering insights relevant for policymakers, scholars, and practitioners.